Human caregiving style and its effect on the dog-human relationship - Habbe, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
Dogs have evolved alongside humans since their domestication 15 000 years ago. No other animal has lived in such close proximity to humans which makes the bond between them unique. The dog-human relationship has started to interest scientists and studies have been performed to investigate the nature of this bond. These studies suggest that the relationship resembles that of the relationship between children and their parents. Furthermore, it has been shown that dogs express attachment behaviour towards their owner and that dogs use their owner as a secure base. However, few studies have looked at how the human’s attachment style and caregiving style may affect the relationship between dogs and humans. In this study, we looked at how the human caregiving style affected the dog-human relationship when faced with different challenging situations. We applied two of the four caregiving styles described in human psychology; the secure caregiving style and the disorganised caregiving style. The dogs interacted with two test persons applying one caregiving style each for 15 days. They were then exposed to challenging situations together with these two persons to investigate which one the dog would choose to seek comfort from. The results showed that when dogs were exposed to the approach of an unfamiliar person they were more oriented towards the person with the secure caregiving style. When the dogs were left alone in a room for three minutes and then reunited with both test persons the dogs initiated more physical contact and spent more time in proximity to the person with the secure caregiving style.